Review: Perawatan Kulit dengan Niacinamide Sebagai Bahan Aktif: A Review: Skin Care with Niacinamide as Active Substance - Vica Aspadiah; Suryani; Wa Ode Sitti Zubaydah; Astrid Indalifiany; Rahmat Muliadi (Fakultas Farmasi Universitas Halu Oleo, 2023)
Skincare is currently important because of the many problems that occur in the skin. Some of the problems that occur have caused a reaction from the community by using several skin care products that are believed to be able to overcome these problems. One of them is Niacinamide. This review aims to summarize the relevant literature on the role and potential of Niacinamide in various skin problems and to compare the results of studies from several articles. We summarize 21 articles obtained from PubMed and NCBI using several keywords. The review results show that Niacinamide is a substance that has particular benefits in the field of skin care product development. Based on literature studies from various studies show that Niacinamide has good potential in overcoming various problems that occur in the skin.